Climate Risk Country Profile : Vietnam - World Bank Group (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
Vietnam is a Southeast Asian nation with an extensive coastline and diverse but generally warm climate including temperate and tropical regions. Given that a high proportion of the country’s population and economic assets are located in coastal lowlands and deltas and rural areas face issues of poverty and deprivation, Vietnam has been ranked among the five countries likely to be most affected by climate change. This document aims to succinctly summarize the climate risks faced by Vietnam. This includes rapid onset and long- term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods and economies, many of which are already underway. Climate change is a major risk to good development outcomes, and the World Bank Group is committed to playing an important role in helping countries integrate climate action into their core development agendas. The World Bank Group (WBG) and the Asian Development Bank (ADB) are committed to supporting client countries to invest in and build a low-carbon, climate resilient future, helping them to be better prepared to adapt to current and future climate impacts.